Grain grinding size of cereals in complete pelleted diets for growing lambs: Effects on animal performance, carcass and meat quality traits - Jaramillo Lopez, Esaul (2019)
The main goal of the present study was to clarify the effects of different grinding particle size of grains (2-mm vs. 6-mm) included in complete pelleted diets (CPD) for fattening lambs on animal performance, carcass and meat quality. Twenty male merino lambs (14.8 kg; n=10 per group) were fed the corresponding diet ad libitum and slaughtered when they reached 27 kg. No differences were observed in the feed conversion ratio or carcass characteristics. However, lambs fed coarser diets (6 mm) were more efficient with less residual feed intake (−14.0 vs. 15.4 g DM/animal/d; P < .05) than lambs fed the 2mm CPD. Lambs fed the 6-mm CPD showed higher levels of intramuscular fat and saturated fatty acids. Consequently, increasing the particle size of the grains included in CPD allows for improving feed efficiency and intramuscular fat in fattening lambs.